Grid connected fuel cell and PV hybrid power generating system design with Matlab Simulink - Bayrak, Gokay; Cebeci, Mehmet (Pergamon-Elsevier Science Ltd, 2014)
Renewable energy sources have been taken the place of the traditional energy sources and especially rapidly developments of photovoltaic (PV) technology and fuel cell (PC) technology have been put forward these renewable energy sources (RES) in all other RES. PV systems have been started to be used widely in domestic applications connected to electrical grid and grid connected PV power generating systems have become widespread all around the world. On the other hand, fuel cell power generating systems have been used to support the PV generating so hybrid generation systems consist of PV and fuel cell technology are investigated for power generating. In this study, a grid connected fuel cell and PV hybrid power generating system was developed with Matlab Simulink. 160 Wp solar module was developed based on solar module temperature and solar irradiation by using real data sheet of a commercial PV module and then by using these modules 800 Wp PV generator was obtained. Output current and voltage of PV system was used for input of DC/DC boost converter and its output was used for the input of the inverter. PV system was connected to the grid and designed 5 kW solid oxide fuel cell (SOFC) system was used for supporting the DC bus of the hybrid power generating system. All results obtained from the simulated hybrid power system were explained in the paper. Proposed model was designed as modular so designing and simulating grid connected SOFC and PV systems can be developed easily thanks to flexible design. Copyright (C) 2013, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: SOFC; Photovoltaic; Microgrid; Hybrid power generating system